FINANCIAL EVALUATION OF PHARMACEUTICAL INDUSTRIES IN INDIA - AN ANALYSIS - A. JALALUDEEN (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Since, most recent two decades economy of India, there is a proceed with inquire about on organization financing exercises, especially planned for seeing how organizations fund their speculations and what source they used to back. By and by, it is seen that money administrators utilize various mixes of obligation and value to meet the different monetary prerequisites of the organization at any rate cost and hazard and for the long haul advantage of the organization. Accordingly, this investigation is expected to make examine of capital structures example of different organizations for the time of 2007-2011 and dissect the impact of changes in capital structure on its speculation design over the timeframe .This examination likewise endeavor to make an intra organization investigation with the goal to decide the significance of obligation value blend for the viable venture arrangement. So also, To examine the financing choices , this paper incorporate the pattern examination of detail money related data of four most rumored pharmaceutical organizations, that are Cipla, Aurobindo Pharma Ltd, Dabur India Ltd, Cadila Health Care Ltd for the time of multi year i;e 2015-2019